Sistem Tanya-Jawab Berbasis Chatbot Web dan Telegram Tentang Akademik UNAND Menggunakan LLM - Wahyudi Wahyudi; Adi Arga Arifnur (Journal of Applied Computer Science and Technology, 2026)
Information about Academic topics, particularly derived from Academic Documents, is crucial. There's a need for an information service that can provide answers to questions concerning contemporary Academic matters. One way to achieve this is by leveraging current technologies, such as the chatbot found on Telegram. Utilizing a Telegram chatbot can lead to the creation of a question-answering system about Academic subjects. Therefore, this research aims to implement a Telegram chatbot-based question-answering system focused on Academic information. This study also utilizes the LangChain method and Large Language Models (LLMs) to create an optimal question-answering system. The research successfully demonstrates its effectiveness in providing answers regarding Academic topics, with the results from User Acceptance Test (UAT) and Black Box Testing indicating that the system can deliver accurate information and functions as intended as a question-answering system for Academic content.